1978
DOI: 10.1139/e78-031
|View full text |Cite
|
Sign up to set email alerts
|

A sub-critical seismic crustal reflection survey over the Aulneau batholith, Kenora region, Ontario

Abstract: A sub-critical seismic reflection survey has been conducted across the Aulneau granite batholith in northwest Ontario. Shot to receiver distances ranged from 2.23 to 71.9 km and the total amount of explosives used for each shot-receiver configuration ranged from 54 to 327 kg. Multiple shots with vertical stacking, frequency filtering and time varying velocity filtering were used to increase the signal to noise ratio for each trace. Reflections from shallow vertical faults and deep horizontal crustal discontinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the region where the Williston Basin is deepest beneath our composite E-W profile (Figure 11) there appears to be a 3-to 4-km decrease in crustal thickness and a related west to east thinning of the lower crustal layer. Low-resolution seismic refraction surveys conducted during the 1960s [e.g., Hajnal, 1969, 1973;Mereu and Hunter, 1969;Gurbuz, 1970] and limited seismic reflection data collected during the 1970s [Green et al, 1978[Green et al, , 1979a have revealed a relatively thin (30-38 km) crust beneath the exposed Superior craton. Differences of 3-5 km between the older crustal thickness estimates and those reported here could result from the lower resolution of the older data and from the different modeling techniques used.…”
Section: Lower Crustal Layermentioning
confidence: 99%
“…In the region where the Williston Basin is deepest beneath our composite E-W profile (Figure 11) there appears to be a 3-to 4-km decrease in crustal thickness and a related west to east thinning of the lower crustal layer. Low-resolution seismic refraction surveys conducted during the 1960s [e.g., Hajnal, 1969, 1973;Mereu and Hunter, 1969;Gurbuz, 1970] and limited seismic reflection data collected during the 1970s [Green et al, 1978[Green et al, , 1979a have revealed a relatively thin (30-38 km) crust beneath the exposed Superior craton. Differences of 3-5 km between the older crustal thickness estimates and those reported here could result from the lower resolution of the older data and from the different modeling techniques used.…”
Section: Lower Crustal Layermentioning
confidence: 99%